2020
DOI: 10.1186/s43088-020-00060-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of some edaphic algae in Egypt

Abstract: Background Algae in general characterized by their rich content of biological compounds. However, few studies were conducted on the soil-inhabiting algae and their antioxidant characteristics. Results The present study was designed to evaluate the antioxidant activity of four edaphic algae including one on-soil alga (Vaucheria geminata) and three axenic isolated in-soil algae (Pleurochloris pyrenoidosa, Botrydiopsis eriensis, and Scenedesmus obliquus). Total antioxidant activity by Phosphomolybdenum assay ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Furthermore, DAMs up-regulated pathways were mainly focused on flavonoid biosynthesis, supporting the results of the significant up-regulated DAMs in the La treatment. Quercitrin is also considered an antioxidant flavonol in algae and plants experiencing metal stress (Skoŕzy ska- Polit et al, 2004;El-Tablawy et al, 2020). Finally, eicosatetraenoic acid is considered an evolutionarily conserved defense signalling molecule that modulates algae and plant stress signalling networks (Shanab et al, 2018;Tan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DAMs up-regulated pathways were mainly focused on flavonoid biosynthesis, supporting the results of the significant up-regulated DAMs in the La treatment. Quercitrin is also considered an antioxidant flavonol in algae and plants experiencing metal stress (Skoŕzy ska- Polit et al, 2004;El-Tablawy et al, 2020). Finally, eicosatetraenoic acid is considered an evolutionarily conserved defense signalling molecule that modulates algae and plant stress signalling networks (Shanab et al, 2018;Tan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Though the induction of antioxidant effects in the prevention and treatment of cancer is obvious, as plants are good sources of antioxidants [ 16 , 17 , 18 ]. A study has shown the antioxidative properties present in soil algae ( Pleurochloris pyrenoidosa , Botrydiopsis eriensis , and Scenedesmus obliquus ) which was attributed to the presence of flavonoid compounds like quercetin [ 19 ]. In addition, another report has described anticancer and antioxidant activities of some algae such as Chlorophyta ( Ulva lactuca , and Codium tomentosum ), Phaeophyta ( Cystoseira crinita , Cystoseira stricta , and Sargassum vulgare ), and Rhodophyta ( Gelidium latifolium , Hypnea musciformis , and Jania rubens ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important previous studies on the genus Vaucheria show its chemical compounds and their importance as antioxidants and antimicrobials according to the results of a spectrophotometer analysis of the total phenolic compounds present in a methanol extract of V. geminata, results were given as gallic acid equivalent (Vuran et al, 2012). In the study El-Tablawy et al (2020), HPLC chromatography was used to identify roughly seven varieties of each phenol and flavonoid chemical in the four algae (Vaucheria geminate, Pleurochloris pyrenoidosa, Botrydiopsis eriensis, and Scenedesmus obliquus). Gallic, chlorogenic, caffeic, and ferulic were the most often found phenols, while rutin, quercetin, apigenin, and quercitrin were the most prevalent flavonoids among all the investigated algae.…”
Section: Introductionmentioning
confidence: 99%